The Effects of Tax Policy on Investment in Agriculture - Halvorsen, Robert (The Review of Economics and Statistics, 1991)
The effects of tax policy on agricultural investment are investigated by estimating a dynamic interrelated input demand system. Net investment is specified to give rise to increasing internal costs of adjustment, resulting in capital inputs being quasi-fixed. The system of demand equations is derived by incorporating a quadratic normalized restricted cost function into a long-run dynamic optimization framework. Copyright 1991 by MIT Press.